Parameterization of oceanic whitecap fraction based on satellite observations - M. F. M. A. Albert; M. D. Anguelova; A. M. M. Manders; M. Schaap; G. de Leeuw; G. de Leeuw; G. de Leeuw (Atmospheric Chemistry and Physics, 2016)
In this study, the utility of satellite-based whitecap fraction (W) data for the prediction of sea spray aerosol (SSA) emission rates is explored. More specifically, the study aims at evaluating how an account for natural variability of whitecaps in the W parameterization would affect SSA mass flux predictions when using a sea spray source function (SSSF) based on the discrete whitecap method. The starting point is a data set containing W data for 2006 together with matching wind speed U10 and sea surface temperature (SST) T. Whitecap fraction W was estimated from observations of the ocean surface brightness temperature TB by satellite-borne radiometers at two frequencies (10 and 37 GHz). A global-scale assessment of the data set yielded approximately quadratic correlation between W and U10. A new global W(U10) parameterization was developed and used to evaluate an intrinsic correlation between W and U10 that could have been introduced while estimating W from TB. A regional-scale analysis over different seasons indicated significant differences of the coefficients of regional W(U10) relationships. The effect of SST on W is explicitly accounted for in a new W(U10, T) parameterization. The analysis of W values obtained with the new W(U10) and W(U10, T) parameterizations indicates that the influence of secondary factors on W is for the largest part embedded in the exponent of the wind speed dependence. In addition, the W(U10, T) parameterization is able to partially model the spread (or variability) of the satellite-based W data. The satellite-based parameterization W(U10, T) was applied in an SSSF to estimate the global SSA emission rate. The thus obtained SSA production rate for 2006 of 4.4  ×  1012 kg year−1 is within previously reported estimates, however with distinctly different spatial distribution.